2021
DOI: 10.34172/aim.2021.107
|View full text |Cite
|
Sign up to set email alerts
|

Primary Liver Cancer in Golestan Province, Northeastern Iran: 13-Year Experience of Golestan Population-Based Cancer Registry (GPCR)

Abstract: Background: Liver cancer (LC) is among the most common and fatal cancers worldwide. A four-fold increasing trend is reported for LC age-standardized mortality rate (ASMR) in Iran within 1990–2015. In the present study, we aimed to report the incidence rate of LC during the 13-year establishment of the Golestan population-based cancer registry (GPCR). Methods: Age-standardized incidence rate (ASIR) per 100000 person-years was calculated using CanReg5 software. The Joint point regression analysis was used to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…So, in developing countries, cancer is a serious and highly prevalent health issue. Current research concluded that 9007 new cancer cases have been reported in Iran from 2004 to 2008 (Roshandel, Sadjadi, Aarabi, Keshtkar, Sedaghat, Nouraie, Semnani, & Malekzadeh, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So, in developing countries, cancer is a serious and highly prevalent health issue. Current research concluded that 9007 new cancer cases have been reported in Iran from 2004 to 2008 (Roshandel, Sadjadi, Aarabi, Keshtkar, Sedaghat, Nouraie, Semnani, & Malekzadeh, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The most common cancer among Iranian population is esophageal squamous cell carcinoma (Roshandel, Sadjadi, Aarabi, Keshtkar, Sedaghat, Nouraie, Semnani, & Malekzadeh, 2012;Mahboubi, Kmet, Cook, Day, Ghadirian, & Salmasizadeh, 1973;Semnani, Sadjadi, Fahimi, Nouraie, Naeimi, Kabir, Fakheri, Saadatnia, Ghavamnasiri, & Malekzadeh, 2006). Risk factors associated with esophageal squamous cell carcinoma is usage of opium, alcohol, tobacco along with poor oral hygiene, hot tea intake as well as obesity Sadjadi, Marjani, Semnani, Nasseri-Moghaddam, 2010;Marjani, Biramijamal, Hossein-Nezhad, Islami, Pourshmas, & Semnani, 2010).…”
Section: Introductionmentioning
confidence: 99%